[Optimization of anesthetic management of peri- and postoperative period in patients under surgical treatment of colorectal cancer. Part I] - Chebanov K.O.; Baranov I.V.; Novikov S.P.; Olefir Y.I.; Grishko S.A.; Vasilishin A.V.; Karas R.K. (Морфологія, 2015)
Background. At the present stage of medicine development colorectal cancer is an actual medical and socio-economical problem. Because surgical is the primary method of treatment the question of how does method of anesthesia and postoperative analgesia influence on the processes of metastasis and survival of cancer patients becomes relevant. Objective. The purpose of research is to select the optimal method of anesthesia protection of patients from operating aggression during surgical treatment of colorectal cancer. Methods. It was performed a comparative analysis of clinical data and results of treatment using total intravenous anesthesia followed analgesia with opiates analgesics, and combined techniques using low-flow sevoflurane anesthesia and epidural analgesia, followed by prolonged epidural anesthesia. Results. It was shown a significant advantage of combined techniques in comparison with total intravenous anesthesia due to: normodynamic type of hemodynamics during operation, possibility to extubate patient in operating room, effective analgesia in early postoperative period. Methods of prolonged epidural analgesia provided a significant need reduction for opioid analgesics, efficient analgesia in postoperative period, saved anti-tumor immunity and resistance to metastasis in patients with cancer, has provided more early resumption of intestine motor function, reduced terms of patient's staying in the intensive care unit. Implemented methodology reduced the frequency of postoperative mortality, complications, average length of hospital stay and frequency of patient returns to intensive care unit. Conclusion. Combined techniques of low-flow sevoflurane anesthesia and epidural analgesia, followed by prolonged epidural anesthesia is an optimal method of anesthesia protection of patients from operating aggression during surgical treatment of colorectal cancer. Citation: Chebanov KO, Baranov IV, Novikov SP, Olefir YI, Grishko SA, Vasilishin AV, Karas RK. [Optimization of anesthetic management of peri- and postoperative period in patients under surgical treatment of colorectal cancer. Part I]. Morphologia. 2015;9(2):85-90. Russian.